Spectrum and trends of cancer among HIV patients in Southwestern Uganda - Raymond Atwine; Mitala Yekosani; Abraham Birungi; Brian Ssenkumba; Barbra Tuhamize; Richard Ezinga; Keneth Male; Taseera Kabanda (PLoS ONE, 2025)
Background Antiretroviral therapy (ART) restores cellular immunity, significantly reducing AIDS-related mortality and morbidity thus improving the quality of life among People living with HIV (PLHIV). Studies done in several countries show a decline in AIDS defining cancers (ADCs) with the introduction of ART however the increased longevity has led to the increase of Non-AIDS defining cancers (NADCs). The study was aimed at studying the changing spectrum and trends of cancer among Human Immunodeficiency Virus (HIV) patients in southwestern Uganda. Methods The study was a retrospective chart review of records of HIV-positive patients attending/receiving care from the Oncology clinic and ISS clinic of Mbarara Regional Referral Hospital (MRRH) who were, diagnosed with cancer for the past 10 years (January 2012–2021). Data were statistically analyzed using STATA version 17 (Stata Corp, Texas, US) at P <  0.05. Results Males were more common at 64.5% while the median age was 37 years (IQR 29–47 years). ADCs were seen in 77.5% of the population while participants with NADCs were older (p < 0.001). The majority 73.3% (283/386) were in later stages (3 and 4). Having either ADCs or NADCs was different across HIV stages (p < 0.001). The median baseline CD4 count was 205 cells/μl (IQR: 90–400 cells/μl). The median duration on ART was 15 months (IQR 3–65 months). Participants with ADCs had been on ART for a shorter duration of time (p < 0.001). Only the outcome of patients with ADCs were available. The outcome varied with sex (p < 0.036), baseline CD4 (p < 0.048), and HIV stage (p < 0.002). Males were more likely to die (30/38 or 78.95%) and lost to follow-up (26/41 or 60.98%). Participants with baseline CD4 cell count > 200 cells/μl were more than twice likely to be active in care. The Commonest ADC was Kaposi Sarcoma (KS) while the commonest NADC was Squamous cell carcinoma, Not otherwise specified. Age above 50 years was associated with a significantly reduced risk of ADCs (OR: 0.11; 95% CI: 0.03–0.43; p value: 0.002). The risk of ADCs increased from stage 2 (OR: 0.46, p-value: 0.03; 95% CI: 0.23–0.91) to stage 3 (OR: 1.13; p-value: 0.66; 95% CI: 0.65–1.97) but this was not statistically significant. The risk of ADCs decreased with increasing ART duration (P value < 0.05). Conclusion ADCs are still a major health challenge in Southwestern Uganda despite the increasing the coverage and uptake of ART in region. These have mostly affected the young people, people who have been on HAART for a shorter period and those with lower CD4 cell count at initiation of ART.